2019
DOI: 10.1002/aur.2242
|View full text |Cite
|
Sign up to set email alerts
|

The Self‐Construal Scale: A Potential Tool for Predicting Subjective Well‐Being of Individuals With Autism Spectrum Disorder

Abstract: Despite accumulating evidence that culture shapes the symptoms of autism spectrum disorder (ASD), no studies have yet applied the Self‐Construal Scale to individuals with ASD. We compared the self‐construals (measured using the Self‐Construal Scale) of 31 high‐functioning Japanese individuals with ASD with those of 60 typically developing (TD) individuals. We also examined how the self‐construals of individuals with ASD related to their intelligence quotient, adverse childhood experiences, attention deficit hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…A review of the literature showed that no studies have already investigated the relationship between SOC and self-construal in parents of children with cancer. But in recent years, studies have been conducted in different parts of the world, including Iran (Ghorbani et al, 2020; Panahipour et al, 2020), South Korea (Jeon et al, 2020), Japan (Kaneko et al, 2020), Italy (Veronese et al, 2021), China (Jin et al, 2021), and the United States (Bakir et al, 2020; Lam & Tran, 2020). And These variables have been measured individually or in relation to other variables and in different target groups.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature showed that no studies have already investigated the relationship between SOC and self-construal in parents of children with cancer. But in recent years, studies have been conducted in different parts of the world, including Iran (Ghorbani et al, 2020; Panahipour et al, 2020), South Korea (Jeon et al, 2020), Japan (Kaneko et al, 2020), Italy (Veronese et al, 2021), China (Jin et al, 2021), and the United States (Bakir et al, 2020; Lam & Tran, 2020). And These variables have been measured individually or in relation to other variables and in different target groups.…”
Section: Introductionmentioning
confidence: 99%